Swine spermatozoa trigger aggregated neutrophil extracellular traps leading to adverse effects on sperm function. (August 2021) - Zambrano, F.; Namuncura, C.; Uribe, P.; Schulz, M.; Pezo, F.; Burgos, R.A.; Taubert, A.; Hermosilla, C.; Sanchez, R.
Highlights: Release of neutrophil extracellular traps is promoted by porcine sperm. The presence of NETs in PMN/sperm co-cultures forms NETs aggregates. Neutrophil extracellular traps negatively affect sperm function. NETs might play a critical role in reduced fertility in swine reproductive technique Abstract: In pigs, the number of PMN in uterus lumen increases within few hours after natural or artificial AI resulting in early PMN-derived innate immune reactions. Sperm-NETs formation was recently reported to occur in various mammalian species. Aim of this study was to investigate direct interactions of boar spermatozoa with swine PMN, the release of sperm-mediated NETs, and to assess NET-derived effects on sperm functionality. Sperm-triggered NETs were visualized by SEM- and immunofluorescence analyses. Sperm-mediated NETosis was confirmed by presence of extruded DNA with global histones and NE. Largest sizes of sperm-mediated agg NETs were detected after 5 h thereby resulting in effective massive sperm entrapment. The number of agg NETs increased from 3 h onwards. Kinetic studies of swine sperm-mediated NETosis showed to be a time-dependent cellular process. In addition, number of NETs-entrapped spermatozoa increased at 3 h of exposure whilst few free spermatozoa were detected after 3 h. Anchored NETs also increased from 3 h onwards. The cytotoxicity of NETs was confirmed by diminution of the total motility and the progressive motility. Spermatozoa membrane integrity and function loss exposed to NETs was confirmed from 3 h. Experiments revealed NETs-derived damaging effects on swine spermatozoa in membrane integrity, motility and functionality. We hypothesize that swine sperm-triggered agg NETs might play a critical role in reduced fertility potential in swine reproductive technique. Thus, agg NETs formation needs to be considered in future studies about uterine environment as well as advance of sperm in the porcine female reproductive tract.